Psychometric properties and factor structure of the persian version of revised prenatal distress questionnaire in second and third trimesters - Maria Esfandiari; Mahbobeh Faramarzi; Hemmat Gholinia; Shabnam Omidvar; Fatemeh Nasiri-Amiri; Somayeh Abdollahi (Wolters Kluwer Medknow Publications, 2020)
Background: There are no proper tools for measuring pregnancy-specific stress in Iranian population. The aim of this study was psychometric evaluation of the Persian version of Revised Prenatal Distress Questionnaire (NuPDQ) for the first time in Iranian society. Materials and Methods: In a descriptive-analytic study, 269 pregnant women completed the NUPDQ at Obstetrics clinics of Mazanderan Province, Iran. The reliability of the 12-item NuPDQ and 17-item NuPDQ was reevaluated using Cronbach's alpha and internal consistency. Concurrent validity was assessed using the Spielberger state-anxiety Inventory. Moreover, exploratory factor analysis was used to assess the structural factors of the questionnaire. Results: Factor analysis revealed that the 12-item NuPDQ consisted of four areas in the second trimester including medical and financial problem, physical symptoms, infant health, and parenting with the explained variance of 64.15%. The Persian version of 17-item NuPDQ consisted of 5 areas in the third trimester, including medical and financial problems, physical symptoms, infant health, parenting, and labor and delivery with an explained variance of 61.94%. In addition, interclass correlation coefficient in all 4 areas and overall scale score exceeded 0.90. Finally, the reliability was high based on Cronbach's alpha of 0.78 for 12-item NuPDQ and 0.79 for 17-item NuPDQ. Conclusions: The Persian version of 12-item NuPDQ in the second trimester and 17-item NuPDQ in the third trimester, as well as all the extracted subscales, had a good validity and reliability for assessing pregnancy-specific stress in Iranian society and can be used in clinical practice.